Implementasi Sistem Pelayanan Pendaftaran Haji Dan Umroh Online Pada PT. Mandiri Mawaddah Nusantara - Yesni Malau - ASM BSI; Adi Surya Putra Ari Ariyanto - STMIK Nusa Mandiri (LPPM Universitas Bina Sarana Informatika, 2014)
PT. Mawaddah Mandiri Nusantara is a new company that specializes in Tour&Travel, where the main businessis booking Hajj and Umrah travel packages, conventional service system which has been running very ineffective and often have problems and consumers also feel difficulty in gettingg information about the products offered. Build an online service system to be implemented in the registration of candidates for Hajj and Umrah pilgrims with a method of object-based programming(PHP Yii Framework), which was created as an information systems solutionof existing problems, by using the online service system will give consumers convenience in transaction and productin formation such as the registration of candidates for the assembly, the payment system, upload the required documents, reports sales of travel packages in the form of graphs and tables, making it easier to conduct business analysis. In addition to the online service system implementation in PT. Mandiri Nusantara Mawaddah used as a marketing medium to reach more consumers with a wider location. Keywords :Onlineregistration, Web, PHP